UPAYA EDUKASI SEDINI MUNGKIN TENTANG SARAF TERJEPIT (HNP) PADA SISWA SMPN 11 PEKANBARU - Mutiara, Sherly; Handoko, Bobi; Arcena, Medyna Putri; Jeprinaldi, Jeprinaldi; Anavira, Sausan (Transpublika Publisher, 2023)
The science of pinched nerves is a very important topic, especially for the general public and parents. However, it should be noted that teenagers can also experience this condition. A pinched nerve occurs when a nerve is compressed by surrounding tissues or structures, which can lead to symptoms such as pain, numbness and paralysis. This article discusses the mechanism by which pinched nerves occur, highlights the risk factors that play a role, and reviews diagnostic and treatment methods. In this context, further research into the prevention and treatment of pinched nerves is crucial to improve the quality of life of patients and reduce their impact on human health. Researchers focused on community outreach as a strategy to disseminate information and knowledge about pinched nerves. This counseling aims to provide the community with a deeper understanding of the symptoms, risk factors, and preventive measures that can be taken. Through this research, it is hoped that a more effective solution can be found in the prevention and treatment of pinched nerves, so as to reduce the incidence of cases and increase public understanding of the importance of maintaining nerve health. Thus, this article makes a positive contribution to disease prevention efforts and improving the overall welfare of the community.